Study on the failure of oil-contaminated wheel-rail conditions - Zhou Gaowei; Zhou Jiajun; Tian Chun; Fei Gao (PLoS ONE, 2025)
The phenomenon of adhesion improvement during wheel-rail sliding has been experimentally verified under water conditions. However, the academic community is in agreement that, for oil that is also fluid, the adhesion characteristic curve under oil conditions exhibits a single peak, making adhesion improvement through wheel-rail sliding impossible. To investigate whether a similar adhesion improvement phenomenon exists under high-viscosity oil medium conditions as observed under water condition, this study conducted wheel-rail adhesion tests on oil-contaminated interfaces within a slip ratio up to 80%. The test results demonstrate that under higher wheel-rail slip, an adhesion improvement phenomenon also occurs on oil-contaminated rail surfaces, although it is more stringent compared to water conditions. The essence of this adhesion improvement is due to the lubrication failure of oil caused by temperature. Finally, this study analyzes the failure conditions of the oil-contaminated interface and its influencing factors, determining the thermal failure temperature range of the oil film.